Gδ-e⋆-locally Continuous and Irresolute Functions via Intuitionistic Fuzzy Topological Spaces - S. Sivasangari, R. Balakumar, G. Saravanakumar (International Journal of Advanced Science and Technology, 2020)
The goal of this paper is to study the concepts of an intuitionistic fuzzy G_δ-e^⋆-locally neighborhood, intuitionistic fuzzy G_δ-e^⋆-locally quasi neighborhood, intuitionistic fuzzy G_δ-e^⋆-locally continuous and intuitionistic fuzzy G_δ-e^⋆-locally irresolute functions in intuitionistic fuzzy topological spaces.Keywords: intuitionistic fuzzy G_δ-e^⋆-locally neighborhood, intuitionistic fuzzy G_δ-e^⋆-locally quasi neighborhood, intuitionistic fuzzy G_δ-e^⋆-locally continuous, intuitionistic fuzzy G_δ-e^⋆-locally irresolute function.